Commercial feeds and temperatures effect on the growth of Carassius auratus (Linnaeus, 1758) oranda juveniles - Ngoh, Chee Ming (2012)
Goldfish Carassius auratus (Linnaeus, 1758) oranda variety is a popular tropical ornamental fish in Malaysia. The aims of this study were to determine the effect of different commercial pellets with different protein levels and temperatures on the growth of juveniles Carassius auratus oranda variety. Feeding and temperature experiments were carried out separately. Protein content of three commercial fish pellets 27, 32 and 42% were confirmed using the Kjeldahl method. Fifteen aquaria (40 X 20 X 20cm) were prepared with 15 replicates. Dechlorinated water was used for all aquarium. Five orandas juveniles were placed in each aquaria. Each experiment was carried out for six weeks. Weight and length increments of these goldfishes were monitored weekly. Results showed that commercial feed 42% protein produced significantly highest (P<0.05) weight increment followed by 32 and then 27% protein. However, there was no significantly different (P>0.05) on the length increment between all treatments. As for the temperature experiment, 27˚C produced sigificant higher (P<0.05) weight increment as compared to 30˚C. However there was no significant (P>0.05) in length increment between treatments. Orandas juveniles had a better growth fed with feed containing 42% protein and culture at temperature of 27˚C.